2002
DOI: 10.1002/jmri.10155
|View full text |Cite
|
Sign up to set email alerts
|

BOLD fMRI of the visual cortex: Quantitative responses measured with a graded stimulus at 1.5 Tesla

Abstract: Purpose: To measure and quantitatively characterize an activity generated by the neurons of the visual cortex (VC) in response to graded luminous intensity contrast stimuli using a 1.5 Tesla scanner. Materials and Methods:Functional magnetic resonance imaging (fMRI) of the vc with the intrinsic blood oxygenation level dependent (BOLD) mechanism was performed by using a paradigm with a 5 ϫ 5 flashing checkerboard pattern flickering eight times per second at eight luminance contrasts presented in a randomized or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Our general finding of a graded BOLD response to increasing stimulus contrast is in agreement with earlier studies using BOLD measurements alone (Boynton et al, 1996; Goodyear and Menon, 1998; Mohamed et al, 2002). Two previous studies have measured both CBF and BOLD responses in human visual cortex to varying stimulus contrast, although these studies were not specifically analyzed to test whether n varies with contrast level.…”
Section: Discussionsupporting
confidence: 92%
“…Our general finding of a graded BOLD response to increasing stimulus contrast is in agreement with earlier studies using BOLD measurements alone (Boynton et al, 1996; Goodyear and Menon, 1998; Mohamed et al, 2002). Two previous studies have measured both CBF and BOLD responses in human visual cortex to varying stimulus contrast, although these studies were not specifically analyzed to test whether n varies with contrast level.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to expectations, activations related to pattern flashes, and also to the visual presentation of letters and to button presses were weaker after HFS. The typical main effects for pattern flashes serve as a visual localizer (Mohamed et al, 2002; Nelles et al, 2002) and together with the responses to the catch trials found in the current study indicate the technical validity. The accurate button presses in responses to catch trials show that subjects were attentive during the task.…”
Section: Discussionsupporting
confidence: 74%
“…There is extensive literature examining the neurophysiologic response to flickering checkerboards at different frequencies, luminance and with different colors (Hoge, Atkinson et al 1999, Vafaee and Gjedde 2000, Mohamed, Pinus et al 2002, Lin, Fox et al 2008), but the literature is sparser on how flow and metabolism in the visual cortex change in response to a more natural and complex stimulus. One study using a James Bond movie found maintained segregation and specialization of functional areas such that this complex movie stimulus and a simple block design stimulus both identified similar visual areas of the brain (Bartels and Zeki 2004).…”
Section: Introductionmentioning
confidence: 99%